Pengembangan Media Pembelajaran Interaktif Articulate Storyline 360 untuk Meningkatkan Hasil Belajar Siswa pada Muatan Pembelajaran IPS Kelas VI SD Negeri Polaman - Sukmawati, Dewi Masyithoh; Sari, Elok Fariha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is a conscious human effort to increase knowledge that is useful for educating and developing the potential of human resources. In the implementation process, learning media is needed that can help the teaching and learning process in the classroom. According to students learning in class during social studies subjects they have not been able to utilize learning media properly so that students have less interest in learning which results in low learning outcomes. The aim of this research is to develop Articulate Storyline 360 learning media on the proclamation of Indonesian independence material to improve student learning outcomes in class VI elementary school. The location of this research was carried out at SDN Polaman, Semarang. This research was conducted using the Research and Development (R&D) method and using the ADDIE model. The research instrument uses a questionnaire sheet and test questions. The methods used to collect data are, observation, interviews, tests, questionnaires. Then the data analysis techniques used in this research are qualitative descriptive analysis, quantitative and inferential statistics. The subjects in the research were students, teachers, media experts and material experts. The results of this research are a significant increase in student learning outcomes and the Articulate Storyline 360 learning media is feasible and effective for use in the student learning process to improve student learning outcomes.